V. I. Lenin on the Place of Marxism in the History of Philosophy - Repšys, Jonas (Problemos, 1971)
The author on the basis of Lenin’s theoretical heritage and Marxist-Leninist conception of the history of philosophy reveals Lenin’s views on the place of Marxism in the development of world philosophical thought. Lenin’s ideas on the relation between Marxism and previous philosophy, on the one hand, and modem non-Marxist philosophy on the other hand, are displayed in the article. By the statement and solution of these questions Leninist principles of the criticism of modern non-Marxist philosophy are disclosed.